2023
DOI: 10.26480/seps.01.2023.11.18
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Covid-19 Pandemic on Livelihood of Rural Community Dwellers in Nigeria

Michael Famakinwa,
Dorcas Lola Alabi,
Damilola Leah Aribifo
et al.

Abstract: The study assessed the effects of covid-19 pandemic on the livelihood of the rural community dwellers in Edo State, Nigeria. A multistage sampling procedure was used to select 156 respondents. Structured interview schedule was used to collect data from the respondents which were subjected to descriptive and inferential analyses. The results revealed that the mean age of the respondents was 47.5 ± 16 years, about 61 percent of the respondents were males and majority (86.5%) had formal education with a mean annu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…COVID-19 was widely reported to have negatively impacted finances in Nigeria. In Edo State Nigeria, 36% of people reported a high negative effect of COVID-19 pandemic on their livelihood [ 48 ], and in Adamawa, Kogi and Oyo state, 83.3% of respondents reported a negative change in customer patronage and 86.6% reported that their business became indebted due to perishable goods in the lockdown period [ 49 ]. In a report by the Jigawa State Internal Revenue Board, the chairman disclosed that the state lost over 20% of the internally generated revenue from 2019 due to tax relief policies instituted during COVID-19 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 was widely reported to have negatively impacted finances in Nigeria. In Edo State Nigeria, 36% of people reported a high negative effect of COVID-19 pandemic on their livelihood [ 48 ], and in Adamawa, Kogi and Oyo state, 83.3% of respondents reported a negative change in customer patronage and 86.6% reported that their business became indebted due to perishable goods in the lockdown period [ 49 ]. In a report by the Jigawa State Internal Revenue Board, the chairman disclosed that the state lost over 20% of the internally generated revenue from 2019 due to tax relief policies instituted during COVID-19 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%